Analisis Pengendalian Internal Atas Piutang pada PT. Usaha Utama Bersaudara - Putri Maulidya; Oryza Tannar (JARUM: Journal of Analysis Research and Management Review, 2024)
The phenomenon that occurs at PT Usaha Utama Bersaudara is the existence of duplicate tasks, where the cashier function is also responsible for the billing function which is only structural in nature. The purpose of this research was to determine whether the internal control over receivables at PT Usaha Utama Bersaudara was in accordance with the COSO framework. This research uses primary and secondary data sources. The data collection methods in this study are interviews, observations, and literature studies. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. The research was conducted at PT Usaha Utama Bersaudara located in Surabaya which is a trading company. The results of the study state that internal control over receivables at PT Usaha Utama Bersaudara is still not in accordance with the COSO Framework. Out of five elements of internal control based on the COSO Framework, only three elements are in accordance, namely risk assessment, information and communication, and monitoring activities. In addition, the existence of duplicate duties and functions that are only structurally written makes internal control over the company's receivables not yet in accordance with the COSO Framework.